Assessment of the 2021 debris flow and flood related loss and damage in Melamchi Watershed of Central Nepal - Duwadi, Subash; Adhikari, Danda Pani; Dhital, Megh Raj; Parajuli, Nuwaraj (Journal of Nepal Hydrogeological Association, 2024)
Nepal, characterized by its youthful mountain ranges, predominantly features mountainous terrain that is geologically fragile and at high risk for prone to geodisasters. Factors such as steep slopes, intense summer rainfall, riverbank erosion, landslide and earthquake contribute to these disasters leading to a significant loss of life and property. This study aims to elucidate the 2021 debris flow and flood-related loss and damage and its impact on local livelihoods in the Melamchi Municipality and Helambu Rural Municipality of Sindhupalchok district. Data were collected through both qualitative and quantitative techniques by using household surveys, focus group discussions, key informant interviews, and field observations were carried out. The sample size was determined by using the Arkon and Colton formula. Disruption of infrastructure, extensive sediment deposition and damage across affected areas, significant erosion, river widening, landscape transformation, temporary river blockage, changes in river morphology, formation of new river channels, and the destruction of agricultural lands were observed in satellite imagery and aerial photographs and they were verified in the field. The event heavily impacted Melamchi Bazaar, claiming over 25 lives and causing substantial damage to the Melamchi Water Supply Project and the Melamchi settlement. The survey revealed that 56% of the respondents lost their agricultural land, 28% lost non-agricultural income sources, 11% lost their employment, and a few others lost other income sources. The total estimated loss of the event was USD 436 million in Melamchi and USD 62 million in Helambu Rural Municipality, including the loss and damage of houses, land, crops, and livestock. Flood and landslides are common phenomena in the Nepal Himalaya and the 2021 Melamchi event was unprecedented in terms of the loss and damage. The result of this study can help policy makers and managers with better planning to minimize the impacts of loss and damage of the geodisaster in the future.